Can fungibility of development aid lead to more effective achievement of the SDGs? An analysis of the aggregate welfare effect of aid fungibility - Zunera Rana; Dirk-Jan Koch (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
In this paper, we explore the relationship between foreign aid fungibility and aggregate welfare. Using panel data from 35 low-income and lower-middle-income countries, we first check the presence of sectoral aid fungibility in our sample and find evidence for it. We then use econometric methods to empirically analyse the impact of this fungibility on aggregate welfare as measured through the Human Development Index. Our findings suggest that in some cases sectoral aid fungibility can lead to an improvement in aggregate welfare. We conclude that recipient governments and donors can consider aid fungibility as a policy tool in ensuring optimal allocation of limited resources to ensure progress towards the sustainable development goals (SDGs).
Keywords: F35; B23; H53; 330; foreign aid; econometrics; aggregate welfare; aid fungibility; Sustainable Development Goals